So you want to study bullying? Recommendations to enhance the validity, transparency, and compatibility of bullying research - Volk, Anthony A.; Veenstra, René; Espelage, Dorothy L. (Aggression and violent behavior, 2017)
Bullying is a serious problem that affects millions of individuals worldwide each year. In response to this, thousands of research articles have been published on bullying. Unfortunately, much of bullying research remains largely atheoretical in its approach to defining bullying as a unique form of aggression. Another key problem in bullying research is the proliferation of heterogeneity of bullying measures whose validity is sometimes questionable. Combined, these two problems have made progress difficult as comparisons between studies and results are impeded by a lack of commonality. As a solution to these problems a discussion of the issues surrounding defining and measuring bullying is offered. This paper aims to promote thoughts and insights about the critical issues and concepts facing those who seek to define and measure bullying for research, intervention, or policy work. Although suggestions for best practices are offered, the overriding goal is to promote all practices that enhance the validity, transparency, and compatibility of bullying research. The time seems right for a general call to action for researchers to individually produce data that are both theoretically and empirically more communicable to the broader bullying community. •Bullying research is increasingly heterogeneous in its definitions & methodologies.•We make recommendations about how to define and measure bullying.•We promote bullying research practices that enhance validity and compatibility.